Integrated monitoring and assessment for air quality management in Hanoi, Vietnam - Hung, Ngo Tho; Steen, Jensen Solvang (VNU Journal of Science: Earth and Environmental Sciences, 2012)
Abstract. In relation to air quality management (AQM), Integrated Monitoring and Assessment (IMA) is defined as a combined usage of measurements and model calculations. Integrated air quality monitoring is monitoring based on results from air quality measurements from fixed monitoring stations, and results obtained from calculations with air quality models. IMA combines data from both modeling and measurements to improve assessment of air quality. A PhD research has been conducted during 2007-2010 with the aim to evaluate air quality models developed inDenmark in the context of AQM inVietnam withHanoi as case study area. TheOperational Street Pollution Model (OSPM) model was adapted to the traffic and vehicle emission conditions inHanoi, and model results were compared to measurement campaigns at three streets where limited measurement data were available. The OSPM model was also used for inverse modeling to estimate average vehicle emission factors based on the air quality measurement data. The OML model was used to assess the geographic distribution of air pollution inHanoi based on an emission inventory for vehicle, domestic and industrial sources. OML model results for urban background conditions were compared to measurements from a passive sample measurement campaign and for hourly pollutant data from an urban background station. The analysis showed many limitations in input data and measurement data but also many opportunities for improving air quality assessment with the use of air quality models in combination with measurements.The paper outlines the concept of IMA and present results from the case study in Hanoi and further provides recommendations for future implementation of IMA in AQM in Hanoi with focus on the role of air quality models. Keywords: Urban air quality management, integrated monitoring, dispersion modeling, OSPM model, OML model.